Experience of Carotid Endarterectomy and its Complications Under Superficial Cervical Block in Conscious Patients in a Tertiary Care Hospital - Khan, Aftab Ahmad; Jamil, Muhammad; Khan, Khurram Shoaib; Ambreen, Shazadi (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To determine the frequency of post-operative complications of carotid endarterectomy conducted under superficial cervical block. Study Design: Cross-sectional study. Place and Duration of Study: Department of Vascular Surgery, Combined Military Hospital, Rawalpindi, Pakistan Sep 2019 to Feb 2021. Methodology: A total of 70 patients who reported to the Vascular Surgery Department, Combined Military Hospital, Rawalpindi Pakistan with an indication for carotid endarterectomy who met the sample selection criteria were included in this study. All patients underwent carotid endarterectomy and were followed up for subcutaneous and subplatysmal hematoma formation, the development of Neuropraxia, stroke and bleeding which required exploration for 4 weeks. Data was analyzed by SPSS 26.0. Results: A total number of 10(14.3%) developed complications while 60(85.7%) surgeries were uneventful. Out of the total complications, hematomas accounted for 4(40%) of cases, while Neuropraxia and contralateral stroke accounted for 2(20%) of the cases each. Of the remaining two cases one developed myocardial infarction (MI) treated by cardiologist and discharged 5th postoperative day while the other required exploration for persistent hemorrhage. Conclusion: Carotid endarterectomy under superficial cervical nerve block is a safe and effective procedure, with good outcomes.